The relative effects of climatic drivers and phenotypic integration on phenotypic plasticity of a globally invasive plant - Chen, Xincong; Wang, Jiayu; Liu, Wenwen; Zhang, Yihui (Frontiers in Plant Science, 2024)
Understanding the constraints of phenotypic plasticity can provide insights into the factors that limit or influence the capacity of an organism to respond to changing environments. However, the relative effects of external and internal factors on phenotypic plasticity remain largely unexplored. Phenotypic integration, the pattern of correlations among traits, is recognized as an important internal constraint to plasticity. Phenotypic plasticity is critical in facilitating the acclimation of invasive species to the diverse environments within their introduced ranges. Consequently, these species serve as ideal models for investigating phenotypic plasticity and its underlying determinants. Here, we collected seeds of a global salt marsh invader Spartina alterniflora from seven invasive populations covering the entire latitudinal range in China. These populations were cultivated in two common gardens located at the southern and northern range margins, respectively. We quantified plasticity and variation therein for plant height, shoot density, first flowering day and inflorescence biomass (on a per capita basis). These traits have direct or indirect effects on invasiveness. We examined the relationships between traits plasticity with climatic conditions at site of origin (external factor) and phenotypic integration (internal factor). We found that plasticity differed according to the trait being measured, and was higher for a trait affecting fitness. Phenotypic variance increased with latitude and temperature at the site of origin was the primary factor affecting phenotypic variation. These results indicated that external abiotic factors directly affected the selection on phenotypic plasticity of S. alterniflora. Our study provides a unique viewpoint on assessing the importance of identifying influential factors and mechanisms underlying phenotypic plasticity. Understanding these factors and mechanisms is a critical indicator for invasive and other cosmopolitan species’ responses, establishment, persistence, and distribution under climate change.